Enrofloxacin Promotes Plasmid-Mediated Conjugation Transfer of Fluoroquinolone-Resistance Gene qnrS - Zhao, Yue; Cao, Zhengzheng; Cui, Luqing; Hu, Tianyu; Guo, Kaixuan; Zhang, Fan; Wang, Xiangru; Peng, Zhong; Liu, Quan; Dai, Menghong (Frontiers in Microbiology, 2022)
This study aimed to determine the effect of enrofloxacin (ENR) on the transfer of the plasmid-mediated quinolone resistance (PMQR) gene qnrS from opportunistic pathogen Escherichia coli (E2) to Salmonella Enteritidis (SE211) and to analyze the resistance characteristics of SE211-qnrS isolates. The plasmid carrying qnrS gene of E2 was sequenced by Oxford Nanopore technology. The plasmid carrying qnrS gene belonged to incompatibility group IncY. In vitro, the transfer experiment of IncY plasmid was performed by the liquid medium conjugation method. The conjugation transfer frequency of the IncY plasmid was 0.008 ± 0.0006 in the absence of ENR, 0.012 ± 0.003 in 1/32 MICENR, 0.01 ± 0.008 in 1/8 MICENR and 0.03 ± 0.015 (Mean±SD) in 1/2 MICENR, respectively. After inoculation of E.coli E2 and SE211, chickens were treated with different doses of ENR (3.03 mg/kg b. w., 10 mg/kg b.w., 50 mg/kg b. w.) for 7 days consecutively. To screen the SE211-qnrS strains from intestinal tract of chickens, the resistance genes and susceptibility of isolates were identified. The amount of E. coli E2 and the copy number of qnrS gene in chicken intestinal tract were determined by colony counting and qPCR, respectively. In vivo, more SE211-qnrS strains were isolated from the treated group compared to the untreated group. SE211-qnrS strains not only obtained IncY plasmid but also showed similar resistance phenotype as E2. In conclusion, ENR treatment can promote the spread of IncY resistance plasmid carrying the qnrS fluoroquinolone resistance gene in Escherichia coli and the development of drug-resistant bacteria.